Exergoeconomic and multi-objective optimization analyses of an organic Rankine cycle integrated with multi-effect desalination for electricity, cooling, heating power, and freshwater production. (1st March 2021) - Mohammed, Ramy H.; Ibrahim, Mostafa M.; Abu-Heiba, Ahmad
Highlights: Exergoeconomic analysis is performed for an integration of ORC, VCR, and MED. The proposed plant produces electricity, cooling, heating power, and freshwater. The proposed plant produces electricity of 10.0 MW at a cost of 0.8087 ¢/kWh. The optimized plant delivers 38.51 m 3 /h freshwater at a price of 0.4225 $/m 3 . Abstract: Efficient utilization of waste heat to run a power and desalination systems is a key technology to mitigate the energy-water crisis. Organic Rankine Cycle (ORC) is one of the promising systems that can exploit low-grade waste heat. So, this paper introduces a novel ORC-based poly-generation system driven by waste heat to produce electrical, cooling, and heating power. The poly-generation system is integrated with multi-effect desalination (MED) system for freshwater production as well. Energy, exergy, and exergo-economic (3E) investigations are made to assess the feasibility of integration of the proposed novel ORC to MED cycle. The new ORC has an adjustable three-way valve to control the seasonal requirement of electrical, heating, and cooling power. Performance of the suggested multi-generation ORC/MED is evaluated by calculating the plant electrical efficiency ( η elec ), energy utilization factor ( E U F ), overall exergy efficiency ( η ex ), total product unit cost ( c p, t o t ), electricity cost C elec, total water price ( T W P ), and exergo-economic factor f k . It is found that the base case of the proposed multi-generation ORC/MED plant could produce electrical power of 8.055 MW at a cost of 1.035 ¢/kWh, cooling power of 5.239 MW, heating power of 7.579 MW, and freshwater of 66.55 m 3 /h for 0.4136 $/m 3 . While the η elec, E U F, η ex, a n d c p, t o t are 13.38%, 53.27%, 37.22%, and 2.877 $/GJ, respectively. The parametric study indicates that adjusting the ratio of electric power generation to cooling power production has a significant impact on the thermo-economic efficiency of the ORC/MED plant and does not have any effect on the freshwater production. The multi-objective optimization analyses show that the electrical power, cooling power and EUF of the optimized case improve by 16%, 306.6% and 50%, respectively, and the c p, t o t and C elec decrease by 16% and 9.5%, respectively.